Gluteus medius activation during running is a risk factor for season hamstring injuries in elite footballers. Issue 2 (February 2017) - Franettovich Smith, Melinda M.; Bonacci, Jason; Mendis, M. Dilani; Christie, Craig; Rotstein, Andrew; Hides, Julie A.
Abstract: Objectives: To investigate if size and activation of the gluteal muscles is a risk factor for hamstring injuries in elite AFL players. Design: Prospective cohort study. Methods: Twenty-six elite male footballers from a professional Australian Football League (AFL) club participated in the study. At the beginning of the season bilateral gluteus medius (GMED) and gluteus maximus (GMAX) muscle volume was measured from magnetic resonance images and electromyographic recordings of the same muscles were obtained during running. History of hamstring injury in the pre-season and incidence of hamstring injury during the season were determined from club medical data. Results: Nine players (35%) incurred a hamstring injury during the season. History of hamstring injury was comparable between those players who incurred a season hamstring injury (2/9 players; 22%) and those who did not (3/17 players; 18%). Higher GMED muscle activity during running was a risk factor for hamstring injury ( p = 0.03, effect sizes 1.1–1.5). There were no statistically significant differences observed for GMED volume, GMAX volume and GMAX activation ( P > 0.05). Conclusions: This study identified higher activation of the GMED muscle during running in players who sustained a season hamstring injury. Whilst further research is required to understand the mechanism of altered muscle control, the results of this study contribute to the developing body of evidence that the lumbo-pelvic muscles may be important to consider in hamstring injury prevention and management.